2017
DOI: 10.3233/nre-162015
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the discrepancy between subjective and objective cognitive impairment following acquired brain injury: The role of psychological affect

Abstract: These findings suggest that an individual's subjective experience of their cognitive difficulties following ABI are not associated with their actual objective cognitive impairment. Clinicians may benefit from considering other possible psychological factors that may play a more crucial role in a patient's appraisals of their cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…This idea is consistent with previous findings (Evans et al, 2008), and qualitative evidence, which suggests that 'emotional difficulties' are often a challenge to developing an alliance (Judd & Wilson, 2005). It is widely acknowledged that emotional distress can impact on processes important in rehabilitation (Coetzer et al, 2018), such as motivation (Siegert & Taylor, 2004) and appraisals of impairment (Byrne, Coetzer, & Addy, 2017). The present study's findings extend this idea, by providing direct evidence that depression also negatively impacts the development of the TA.…”
Section: Depression Is a Significant Predictor But Not In All Casessupporting
confidence: 88%
“…This idea is consistent with previous findings (Evans et al, 2008), and qualitative evidence, which suggests that 'emotional difficulties' are often a challenge to developing an alliance (Judd & Wilson, 2005). It is widely acknowledged that emotional distress can impact on processes important in rehabilitation (Coetzer et al, 2018), such as motivation (Siegert & Taylor, 2004) and appraisals of impairment (Byrne, Coetzer, & Addy, 2017). The present study's findings extend this idea, by providing direct evidence that depression also negatively impacts the development of the TA.…”
Section: Depression Is a Significant Predictor But Not In All Casessupporting
confidence: 88%
“…In a more recent assessment-based study, ABI participants' subjective reports of cognitive impairment were found to be unrelated to objective cognitive measures. However, their subjective impairments were closely related to self-reported depression and anxiety, suggesting that emotion, rather than objective impairment, may be an important influence on patients' appraisals of their cognitive impairments (Byrne, Coetzer & Addy, 2017). However, with time, and with the NWBIS becoming more active in delivering an assessment and rehabilitation service to increasing numbers of patients with acquired brain injury, more novel research questions started to emerge from our daily clinical practice.…”
mentioning
confidence: 99%
“…Note that this pattern of results was as well replicated in people across various conditions other than psychosis. For instance, elder adults with mild cognitive decline (Lehrner et al, 2016), people with chronic fatigue syndrome (Cockshell & Mathias, 2014) and individuals following acquired brain injury (Byrne, Coetzer, & Addy, 2017) were found to have minimal associations between subjective cognitive ability and object performances on neurocognitive tests.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, depression as a predictor of SCI was also reported in other conditions. For instance, Byrne et al () has recently demonstrated that depression is positively correlated with SCI domains in people following acquired brain injury.…”
Section: Discussionmentioning
confidence: 99%